2021
DOI: 10.1029/2020je006737
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Forcing of the Nocturnal Near Surface Environment by Martian Water Ice Clouds

Abstract: The Mars Science Laboratory (MSL) landed on Mars in Gale crater in 2012, and, since then, the rover has been almost continuously observing the meteorology within the crater using the Rover Environmental Monitoring Station (REMS; Gómez-Elvira et al., 2012). Among the regular observations by REMS have been surface pressure, UV radiation flux, air temperature, humidity, and ground temperature (measurements of wind speed and direction were constrained to moments when the wind was blowing onto the front of the rove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Similar investigations into radiatively active water-ice clouds have taken place at other mission locations, such as the Mars Science Laboratory rover (Grotzinger et al 2012). Notably, perturbations in the minimum daily ground and air temperatures were detected in the record of the REMS instrument (Gómez-Elvira et al 2012) in Gale Crater (Cooper et al 2021). These perturbations consisted of an increase in the minimum overnight ground and air temperatures, particularly during the Aphelion Cloud Belt (ACB) season.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Similar investigations into radiatively active water-ice clouds have taken place at other mission locations, such as the Mars Science Laboratory rover (Grotzinger et al 2012). Notably, perturbations in the minimum daily ground and air temperatures were detected in the record of the REMS instrument (Gómez-Elvira et al 2012) in Gale Crater (Cooper et al 2021). These perturbations consisted of an increase in the minimum overnight ground and air temperatures, particularly during the Aphelion Cloud Belt (ACB) season.…”
Section: Introductionsupporting
confidence: 56%
“…Unlike the study from Cooper et al (2021), where ground and air temperatures are recorded by instruments on board Curiosity and both temperatures are used in their analysis, Phoenix did not carry a ground temperature sensor. Because of this, the surface energy balance is used as input to model the subsurface heat conduction at the Phoenix landing site to estimate ground temperature.…”
Section: Surface Energy Balancementioning
confidence: 99%
See 1 more Smart Citation
“…The peak cloud activities, determined by cloud opacity, were observed in the morning/afternoon and around the ACB period (Kloos et al 2018). They have also been reported to leave a thermal signature at night on Gale's surface (Cooper et al 2021), again demonstrating the importance of the radiative impact of water-ice clouds on the lower atmosphere as well as on the surface.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to gravity waves, which cause temperature swings in the lower Martian atmosphere, the observations by the Curiosity rover showed that topographical effects can induce temperature fluctuations [12]. Moreover, the nighttime thermal forcing can be affected by the presence of clouds [13].…”
Section: Introductionmentioning
confidence: 99%